Menciptakan Keunggulan Bersaing Berkelanjutan Berbasis Sumber Daya Manusia dalam Dunia Pendidikan - Rahmadani Rahmadani; Siti Qomariah (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2022)
The Covid-19 pandemic has changed many things, including the transition to conventional activities that must be done digitally. The Indonesian Ministry of Education and Culture has set a policy that education must continue during the pandemic but with a different system (study from home) by utilizing technology (online). Changes in the current era are forcing the world of education to change the old paradigm that puts humans not the main thing in an organization. Still, humans are now considered essential items in an organization. The new human paradigm is an important asset, so to create a competitive advantage in the world of education, the strategy used is a human resource management strategy. The method used in this research is the literature study or literature study. A reasonable and appropriate human resource management strategy that focuses on improving the capabilities and competencies of its human resources makes institutions engaged in education able to compete and survive changing conditions. For character building and performance, it can be done by applying KASAH (Knowledge, Ability, Skill, Attitude, Habit) to gain a competitive advantage.